Effects of weighted vests versus elastic bands plyometric jump training on lower-body physical performance adaptations in volleyball players - Bao, Y.; Qiao, Y.; Yang, S. (Frontiers in Physiology, 2026)
Introduction: The aim of this study was to investigate the impact of different plyometric jump training (PJT) loading strategies, using either weighted vests (WV) or elastic bands (EB), on the physical and physiological performance of young volleyball players.